Misidentification of Type of Lightning Flashes in Malaysia - Puteri Nur Suhaila Ab Rahman; Zikri Abadi Bharudin; Nur Hidayu Abdul Rahim (Institute of Advanced Engineering and Science, 2014)
The Lightning Detection System (LDS) system monitored by Malaysian Meteorological Service (MMS) and Tenaga Nasional Berhad (TNB) are not reliable that may due to unresolved site errors .From informal observation, Baharudin and co-workers found the data recorded by TNB was not identical to their data. In this paper,we observed about Lightning Flashes in Malaysia nearly 21 data matching the time and date of our data with data from TNB Reports that the lightning flash polarity between both data has a negative polarity, but there are differences on multiplicity. Regarding data from TNB Reports , they also noted that there was presented a total of 10 positive cloud-to-ground flash data , but we did not find any data positive cloud-to-ground flash data. However, the data we have found a total of 191 data were presented from cloud flash but TNB did not record any cloud flash.